The Rapidity Distributions and the Thermalization Induced Transverse Momentum Distributions in Au-Au Collisions at RHIC Energies - Zhi-Jin Jiang; Jia-Qi Hui; Yu Zhang (Advances in High Energy Physics)
It is widely believed that the quark-gluon plasma (QGP) might be formed in the current heavy ion collisions. It is also widely recognized that the relativistic hydrodynamics is one of the best tools for describing the process of expansion and hadronization of QGP. In this paper, by taking into account the effects of thermalization, a hydrodynamic model including phase transition from QGP state to hadronic state is used to analyze the rapidity and transverse momentum distributions of identified charged particles produced in heavy ion collisions. A comparison is made between the theoretical results and experimental data. The theoretical model gives a good description of the corresponding measurements made in Au-Au collisions at RHIC energies.